New urban development : looking back to see forward - Gruen, Claude (Rutgers University Press, 2010)
The recent recession is one result of how local planning laws and practices have stifled competition, discouraged innovation, and artificially pushed up prices in America's most economically vibrant regions. Economist and consultant Claude Gruen unravels the story behind how these unintended consequences have resulted from the evolution of local zoning, growth controls, and laws intended to increase housing affordability.